Profil kecanduan smartphone pada siswa - Adelia Rosita; Sri Utami; Rezky Permata Sari (Orien: Cakrawala Ilmiah Mahasiswa, 2022)
one of the real impacts of technological developments is the inability of individuals to be separated from their devices. This form of disability is reflected in the behavior of smartphone addiction. This study aims to determine the profile of smartphone addiction in students. The population in this study were students of class X and XI of SMKS Muhammadiyah 11 Jakarta with a total of 160 students. The sample was drawn randomly with the sample size estimated using the Slovin formula at a degree of error of 10% with a total of 62 students. Data were collected through a smartphone addiction scale. The data were analyzed descriptively with the percentage formula. The results showed that smartphone addiction in students was in the moderate category. Further efforts from Guidance and Counseling teachers are needed to reduce the level of addiction.